Arguments to Support a Viral Origin of Oral Squamous Cell Carcinoma in Non-Smoker and Non-Drinker Patients - Foy, Jean-Philippe; Bertolus, Chloé; Boutolleau, David; Agut, Henri; Gessain, Antoine; Herceg, Zdenko; Saintigny, Pierre (Frontiers in Oncology, 2020)
In western countries, an increasing incidence of oral squamous cell carcinoma (OSCC) has been observed in non-smoker non-drinker patients (NSND), mostly in women with HPV-negative OSCC. In the context of the unknown etiology and mechanisms of tumorigenesis of OSCC in NSND, we discuss data supporting the hypothesis of a viral origin not related to HPV. OSCC from NSND are characterized by an antiviral DNA methylation and gene expression signature. Based on the similar increasing incidence of OTSCC and OPSCC in young women and men respectively, we hypothesize that changes in sexual behaviors may lead to an increasing incidence of herpesvirus in the oral cavity, especially HSV-2, similarly to what has already been described in HPV-positive OPSCC. Because viral genome integration has not been detected in OSCC from NSND, a “hit and run” viral mechanism involving epigenome deregulation could therefore play a key role at early steps of oral carcinogenesis in this population of patients. In conclusion, epidemiological, clinical and molecular data supports a “hit and run” viral origin of OSCC from NSND.